Infected Thyroglossal Duct Cyst Involving Submandibular Region: A Case Report - Rahul A. Gandhi; Rahul Bhowate; Shirish Degweker; Arvind Bhake (Hindawi Limited, 2011)
Thyroglossal duct cyst presents most frequently in the midline of the neck, either at or just below the level of the hyoid bone. They generally manifest as painless neck swelling, and they move on protrusion of tongue and during swallowing. A case of thyroglossal cyst was reported in the left submandibular region in a 14-year-old girl, above the level of hyoid bone; ultrasound examination favored a cystic lesion which moved in a vertical fashion on swallowing whereas fine needle aspiration cytology report was suggestive of simple cystic lesion of thyroglossal cyst. No lymphoid or malignant cells were present. The cyst was excised completely by surgical procedure under general anesthesia. Histopathological analysis revealed thyroglossal cyst showing columnar and flattened epithelium of cyst with focal aggregate of chronic inflammatory cells supported by fibrocollagenous cyst wall. The clinical, ultrasound, and histopathological findings suggested that the lesion was an infected thyroglossal cyst. There was no evidence of recurrence 6 months after surgery.